Use of Rubber Mat to Improve Deformation Behaviors of Ballastless Tracks Laid on Bridges. (17th August 2020) - Zheng, Weiqi; Sheng, Xingwang; He, Hongqiang; Xu, Hongyi; Yang, Ying
Abstract : The deformation behaviors of ballastless tracks have an important influence on their service performance. In this work, rubber mats commonly used in metro traffic were employed in ballastless tracks laid on bridges to improve their deformation behaviors. In order to research the effect of rubber mat for deformation behaviors, a series of static loading tests were carried out based on two full-scale ballastless tracks with different types of isolation layers. Main conclusion include that, for ballastless track with geotextile isolation layers, gaps and voids are formed at interlayers with the increasing static load. However, for ballastless track with rubber mat isolation layer, the maximum tensile deformation in the thickness direction unexceeds the precompression of rubber mat under the deadweight of its upper structures. Interlayer gaps and voids can be eliminated due to the precompression of rubber mat. Besides, the rubber mat isolation layer is still in the linear elasticity stage under the routine service condition, and the interlayer behaviors of the ballastless tracks perform well. It is a feasible way to use a rubber mat isolation layer to improve the deformation behaviors of ballastless tracks laid on bridges.